Syphilitic Coronary Artery Ostial Stenosis Resulting in Acute Myocardial Infarction Treated by Percutaneous Coronary Intervention - Marcelo A. Nakazone; Maurício N. Machado; Raphael B. Barbosa; Márcio A. Santos; Lilia N. Maia (Case Reports in Medicine)
Cardiovascular abnormalities are well-known manifestations of tertiary syphilis infections which although not frequent, are still causes of morbidity and mortality. A less common manifestation of syphilitic aortitis is coronary artery ostial narrowing related to aortic wall thickening. We report a case of a 46-year-old male admitted due to acute anterior ST elevation myocardial infarction submitted to primary percutaneous coronary intervention successfully. Coronary angiography showed a suboccluded ostial lesion of left main coronary artery. VDRL was titrated to 1/512. The patient was discharged with treatment including benzathine penicillin. Previous case reports of acute myocardial infarction in association with syphilitic coronary artery ostial stenosis have been reported, but the fact that the patient was treated by percutaneous coronary intervention is unique in this case.